2015
DOI: 10.4103/1117-6806.162590
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and prostate cancer in Southern Nigeria: A preliminary report

Abstract: Introduction:The natural history of prostate cancer varies among patients. The aim of this study is to detect any variations in clinical and pathological characteristics of the tumor in patients from different ethnic groups in Southern Nigeria.Patients and Methods:Consecutive patients who presented with features of prostatic diseases at the Urology Units of University of Port Harcourt Teaching Hospital, Port Harcourt and Nnamdi Azikiwe University Teaching Hospital, Nnewi, were evaluated prospectively with hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…An analysis of men with Pca from the various ethnic groups in Southern Nigeria by Sapira et al showed that most of the men presented with advanced and metastatic disease. Also, adenocarcinoma was the commonest histologic type [33]. These findings were also documented by other workers [11,17,34].…”
Section: Discussionsupporting
confidence: 84%
“…An analysis of men with Pca from the various ethnic groups in Southern Nigeria by Sapira et al showed that most of the men presented with advanced and metastatic disease. Also, adenocarcinoma was the commonest histologic type [33]. These findings were also documented by other workers [11,17,34].…”
Section: Discussionsupporting
confidence: 84%